Some elements and fatty acid profiles of three different edible mushrooms from Tokat province in Turkey - Bengu, Aydın Sukru (Progress in Nutrition, 2019)
Three wild edible mushrooms species were collected from the Tokat district to determine fatty acid profiles and some microelement contents. According to analyze results, the highest amount of Fe was found in Coprinus atramentarius, Cu was in Suillus luteus. The dominant fatty acid at all mushroom species was Oleic acid and the next three acids were Linoleic, Palmitic and Stearic acid ranging from 7.73-33.17%, 21.24-28.60% and 10.49-28.55% respectively. In addition to these acids, seven different kinds of fatty acids have been investigated too in this research. The results of the study showed that Coprinus atramentarius, Laetiporus sulphureus and Suillus luteus species have a rich measure of fatty acids and microelements.